2002
DOI: 10.1063/1.1456257
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport measurements of Schottky barrier inhomogeneities

Abstract: We report nonmonotonicities in the low-temperature current versus gate voltage characteristics of PtSi/Si Schottky Barrier metal–oxide–semiconductor field-effect transistors. Direct tunneling through the Schottky barrier is shown to limit the current and be superimposed with resonant peaks and oscillations. These structures are attributed to resonant tunneling through impurities located close to the interface and nonuniformities of the heterojunction. We thus demonstrate barrier height variations in electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…This may be due to the sensitivity of the Schottky interfaces to preparation procedures and to different techniques of measuring the BH [17]. In recent years, studies of SBH inhomogeneities have been carried out [16,19,[23][24][25][26][27][28][29][30]. Freeouf et al [23] reported on the influence of a small patch with a low BH within the contact area on the ideality factor and the essence of the contact area size in this effect.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the sensitivity of the Schottky interfaces to preparation procedures and to different techniques of measuring the BH [17]. In recent years, studies of SBH inhomogeneities have been carried out [16,19,[23][24][25][26][27][28][29][30]. Freeouf et al [23] reported on the influence of a small patch with a low BH within the contact area on the ideality factor and the essence of the contact area size in this effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this regime, single dopant atoms have been demonstrated to dominate the behavior of downscaled versions of conventional devices. 1 On the other hand, the promising opportunity is offered to study the physics of semiconductors on their ultimate length scale by addressing separate dopants. Putting a small gate close to a single impurity would, for example, allow for the manipulation of individual hydrogenlike wave functions.…”
mentioning
confidence: 99%
“…However, tunneling spectroscopy of impurity states can also be done with microfabricated devices, such as nano-sized Schottky diodes [40], nanosized field effect transistors [41][42][43][44] or nanosized memristors [45]. In this work, we present an observation of Shiba bound states forming in a dopantinduced impurity band.…”
mentioning
confidence: 82%